Perbaikan Karakteristik Tepung Keladi Hitam Varietas Lokal Kalimantan Barat Melalui Fermentasi Umbinya dan Pemanfaatannya pada pembuatan Cake - Susana Susana; Lamria Mangunsong; Iwan Rusiardy (Politeknik Negeri Pontianak, 2019)
Black tuber of local varieties of Kalimantan is one of a group of tubers that are rich in carbohydrates. Its use as a processed product is still limited and has constraints, including bitter taste and a little itching, low viscosity, low solubility and a less stable gel forming ability. Therefore, modification of black tuber tuber fermented is one way to overcome the limitations that exist in taro tuber so that it can be further processed into flour and used as a substitute for wheat flour. The purpose of this study is 1) to study the characteristics of black tuber of local fermented varieties including total dissolved solids, alcohol content, pH value, 2) studied the characteristics of black taro flour local varieties whose tuber fermentation included increased viscosity, gel strength, swelling power, and ease of dissolution. 3) studying the characteristics of modified local varieties of black tuber tuber modified by fermentation from the best treatment including flower and organoleptic power (color, taste, texture, pore) The stages in this study include making black taro tuber tape with variations in the concentration of yeast tape 0.125% (K1), 0, 25% (K2), 0.375% (K3), 0.5% (K4) and fermentation duration 24 hours, 48 ​​hours, and 72 hours with sample codes T1, T2 and T3. Next, the process of combing the fermented black taro tubers is carried out. The best treatment was 0.25% yeast concentration with 24-hour fermentation time and based on swelling power of 4.4296, then applied as a substitute for wheat flour in cake making with a ratio of 30: 70, 50: 50, 70: 30 (ratio Fermented tuber tuber flour: Wheat flour.